2020
DOI: 10.5937/zembilj2001021g
|View full text |Cite
|
Sign up to set email alerts
|

Some physical properties of long-term irrigated fluvisols of valley the river Beli Drim in Klina (Serbia)

Abstract: Physical properties of long-term irrigated fluvisols, Gajić et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Although many authors reported the transformation of drained alluvial soils towards the development of mollic or cambic horizons, which excluded these soils from Fluvisols group according to the statements of WRB classification, Fluvisols are still reported from regulated and drained valleys [10][11][12]32,54,55]. This may indicate that many authors still apply the term "Fluvisols" as a synonym of alluvial soils on the Holocene river terraces, irrespective of the actual stage of their pedogenic transformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many authors reported the transformation of drained alluvial soils towards the development of mollic or cambic horizons, which excluded these soils from Fluvisols group according to the statements of WRB classification, Fluvisols are still reported from regulated and drained valleys [10][11][12]32,54,55]. This may indicate that many authors still apply the term "Fluvisols" as a synonym of alluvial soils on the Holocene river terraces, irrespective of the actual stage of their pedogenic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important factors in the variability of valley and/or floodplain ecosystems are soils composed of spatially and vertically differentiated alluvial sediments [6][7][8]. Sedimentation conditions can significantly change over time; therefore, stratification is a basic feature of valley/floodplain soils, affecting their physicochemical and water properties, as well as the productivity of alluvial soils [9][10][11][12]. Moreover, the sequences of sediment layers and soil horizons in the soil profiles on floodplain terraces demonstrate the successions of stable periods with distinct pedogenesis and unstable (i.e., geomorphologically active) periods, in which fresh alluvial layers were accumulated [6,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na uzorcima u narušenom stanju određene su sledeće hemijske osobine zemljišta: aktivna kiselost (pH u H2O), razmenljiva kiselost (pH u 1M KCl), sadržaj humusa, hidrolitička kiselost (H), suma razmenljivoadsorbovanih baznih katjona (S), totalni kapacitet adsorpcije katjona (CEC) i stepen zasićenosti bazama (V). Navedene fizičke i hemijske osobine zemljišta određene su standardnim postupcima (Gajić, 2005;Dugalić i Gajić, 2005). Sadržaji pristupačnog kalijuma (K2O) i fosfora (P2O5) određeni su Al-metodom po Egner-Rejmu-Domingu (Минеев и сар., 2001).…”
Section: Methodsunclassified
“…and 'depressive' Żuławy situated below sea level were distinguished (Witek, 1965;Piaścik et al, 2000). Alluvial soils are the soils that show great variability in terms of morphology, physicochemical properties, water retention properties and productivity (Skuodiene et al, 2016;Kercheva et al, 2017;Dezső et al, 2019;Gajić, 2020). They occur in river valleys and delta areas, and show large spatial differentiation (Ligęza, 2016).…”
Section: Introductionmentioning
confidence: 99%